An Alternative to the Sandmeyer Approach to Aryl Iodides. Issue 17 (10th March 2015) - Hu, Bao; Miller, William H.; Neumann, Kiel D.; Linstad, Ethan J.; DiMagno, Stephen G.
Abstract Iodoarenes are important synthons for a wide range of organic transformations. Here we report a general strategy to prepare singly iodinated electron‐rich aromatic compounds through the intermediacy of diaryliodonium salts. This process, which incorporates a phase separation that greatly simplifies product purification, is an attractive replacement for the Sandmeyer approach to iodoarenes that are otherwise difficult to access.